Cost-effectiveness of a risk-stratified approach to cardiac resynchronisation therapy defibrillators (high versus low) at the time of generator change. Issue 5 (29th September 2017) - Claridge, Simon; Sebag, Frederic A; Fearn, Steven; Behar, Jonathan M; Porter, Bradley; Jackson, Tom; Sieniewicz, Benjamin; Gould, Justin; Webb, Jessica; Chen, Zhong; O'Neill, Mark; Gill, Jaswinder; et al.
Abstract : Objective: Responders to cardiac resynchronisation therapy whose device has a defibrillator component and who do not receive a therapy in the lifetime of the first generator have a very low incidence of appropriate therapy after box change. We investigated the cost implications of using a risk stratification tool at the time of generator change resulting in these patients being reimplanted with a resynchronisation pacemaker. Methods: A decision tree was created using previously published data which had demonstrated an annualised appropriate defibrillator therapy risk of 2.33%. Costs were calculated at National Health Service (NHS) national tariff rates (2016–2017). EQ-5D utility values were applied to device reimplantations, admissions and mortality data, which were then used to estimate quality-adjusted life-years (QALYs) over 5 years. Results: At 5 years, the incremental cost of replacing a resynchronisation defibrillator device with a second resynchronisation defibrillator versus resynchronisation pacemaker was £5045 per patient. Incremental QALY gained was 0.0165 (defibrillator vs pacemaker), resulting in an incremental cost-effectiveness ratio (ICER) of £305 712 per QALYs gained. Probabilistic sensitivity analysis resulted in an ICER of £313 612 (defibrillator vs pacemaker). For reimplantation of all patients with a defibrillator rather than a pacemaker to yield an ICER of less than £30 000 per QALY gained (current NHS cut-off for approval of treatment), the annual arrhythmic event rate would need to be 9.3%. The budget impact of selective replacement was a saving of £2 133 985 per year. Conclusions: Implanting low-risk patients with a resynchronisation defibrillator with the same device at the time of generator change is not cost-effective by current NHS criteria. Further research is required to understand the impact of these findings on individual patients at the time of generator change.